Atividade biológica de extratos de Cabralea canjerana sobre Anastrepha fraterculus e Spodoptera frugiperda - Magrini, Flaviane Eva (My University, 2014)
Many reports in the literature indicated that representatives of Meliaceae, including neem, have secundary metabolites with important biological activities on insects. Cabralea canjerana is a widely distributed America native tree from Meliacaea, witch it is and used in indigenous medicine, due to its therapeutic properties. Among the major insect pests associated with agricultural production in South America, stand out the South American fruit fly - Anastrepha fraterculus and the fall armyworm Spodoptera frugiperda. This study evaluated the effects of C. canjerana ethyl acetate and ethanol extracts of mature fruits and their seeds on the intake and oviposition the adults of A. fraterculus and on eggs, larvae and pupae of S. frugiperda. The ethyl acetate fruit extract added to an artificial diet (5mg/mL), within 48 hours, was significantly more effective than the other evaluated extracts, inducing 69.42% mortality of the flies. All extracts caused oviposition deterrence, significantly reducing the number of flies in papaya fruit. Among other biological effects on A. fraterculus was found that the ethyl acetate fruit extract, induced larval mortality, occurrence of larviform pupae and abnormal adults. All extracts induced antifeedant and larvicidal activity of S. frugiperda at concentrations of 500 and 1000 ppm. The ethyl acetate seed extract at 1000 ppm was the most active one, inducing both larval and embryonic mortality (100% and 69%, respectively). From its fractionation on Colum Chromathography five fractions were obtained. From these obtained fractions, the third one, composed principally of triterpenes induced larval mortality three times higher than the crude extract. All extracts and fractions significantly altered the life cycle, the larval weight and induced the occurrence of various abnormalities on S. furgiperda larvae and pupae. The greater activity of seed extracts and fruit of C. canjerana obtained with ethyl acetate indicates the presence of limonoids and triterpenes with biological activity that can potentially come to be used in the management of A. fraterculus. and S. frugiperda.
Estudos têm indicado que representantes de Meliaceae, incluindo o neem, apresentam metabólitos secundários com importante atividade biológica sobre insetos. Cabralea canjerana é uma Meliacaea arbórea endêmica da América e de ampla distribuição, utilizada na medicina indígena, devido as suas propriedades terapêuticas. Dentre os principais insetos-praga associados à produção agrícola da América do Sul, destacam-se a mosca-das-frutas-sul-americana - Anastrepha fraterculus e a lagarta-do-cartucho-do-milho - Spodoptera frugiperda. Este estudo objetivou avaliar os efeitos de extratos de frutos e sementes de C. canjerana obtidos em acetato de etila e etanol sobre a ingestão e a oviposição de adultos de A. fraterculus e sobre ovos, larvas e pupas de S. frugiperda. O extrato de fruto (acetato de etila), adicionado a dieta artificial (5mg/mL), em 48h, foi significativamente mais efetivo, induzindo 69,42% de mortalidade das moscas. Todos os extratos provocaram deterrência de oviposição, reduzindo significativamente o número de moscas por fruto de mamão papaia. Entre os demais efeitos biológicos sobre A. fraterculus verificou-se que o extrato de fruto (acetato de etila), induziu a mortalidade larval, ocorrência de pupas larviformes e de adultos anormais. Todos os extratos induziram atividade antialimentar e larvicida à S. frugiperda nas concentrações de 500 e 1000 ppm. O extrato de semente (acetato de etila), a 1000 ppm, foi o mais ativo, induzindo mortalidade larval e embrionária (100% e 69%, respectivamente). Do seu fracionamento em coluna de cromatografia foram obtidas cinco frações. A partir destas frações, a terceira, composta principalmente por triterpenos induziu mortalidade larval três vezes maior do que o extrato bruto. Todos os extratos e frações alteraram significativamente a duração do ciclo, do peso larval e induziram a ocorrência de diversas anormalidades larvais e pupais em S. furgiperda. A maior atividade dos extratos de semente e de fruto de C. canjerana, obtidos com acetato de etila indica a presença de limonóides e triterpenos com atividade biológica que, potencialmente podem vir a ser utilizados no manejo de A. fraterculus e S. frugiperda.
Keywords: Biotecnologia; Mosca-das-frutas; Meliacea